Assuming Access to Professional Advice. Issue 4 (2021) - Haupt, Claudia E.
Abstract: Access to reliable health advice can make the difference between life and death. But good advice is hard to come by. Within the confines of the professional-client or doctor-patient relationship, the First Amendment operates in a way that protects good and sanctions bad advice. Outside of this relationship, however, the traditional protections of the First Amendment prohibit content- and viewpoint discrimination. Good and bad advice are treated as equal. A core assumption of First Amendment theory is the autonomy of speakers and listeners. Another assumption, as this Article demonstrates in the health context, is the availability of access to professional advice. This assumption, however, is erroneous because access to health advice in fact is unevenly distributed. This Article argues that assuming access to professional advice creates indefensible inequality. Lack of access to expert advice puts some listeners at much higher risk than others. Current First Amendment doctrine is largely unproblematic for those who can afford expert advice, and makes expert advice much costlier where health provider access is needed to obtain good advice. Those who lack access must place a higher degree of trust in widely-available information because they have no more reliable alternative. In other words, First Amendment doctrine places a higher burden on those who can least afford expert advice and who are most dependent on experts in public discourse.